The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3390/ijms131115305
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Evaluation and Preliminary Pharmacokinetics Studies of a New Diclofenac Prodrug without Gastric Ulceration Effect

Abstract: Long-term nonsteroidal anti-inflammatory drugs (NSAIDs) therapy has been associated with several adverse effects such as gastric ulceration and cardiovascular events. Among the molecular modifications strategies, the prodrug approach is a useful tool to discover new safe NSAIDs. The 1-(2,6-dichlorophenyl)indolin-2-one is a diclofenac prodrug which demonstrated relevant anti-inflammatory properties without gastro ulceration effect. In addition, the prodrug decreases PGE2 levels, COX-2 expression and cellular in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
(41 reference statements)
3
10
0
Order By: Relevance
“…This result supports previous findings that masking the carboxylic acid moiety of NSAIDs gives safer compounds [5,11]. …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This result supports previous findings that masking the carboxylic acid moiety of NSAIDs gives safer compounds [5,11]. …”
Section: Resultssupporting
confidence: 93%
“…Previous studies have reported other forms of diclofenac prodrugs with lower GI adverse effects, or with properties that aid delivery of the drug to certain distal body organs. For example, 1-(2,6-dichlorophenyl)indolin-2-one is a diclofenac prodrug which demonstrated relevant anti-inflammatory properties without GI ulceration effect [ 11 , 12 ]. Diclofenac ester prodrugs were found to be potent anti-inflammatory drugs with less ulcerogenic potential than the parent diclofenac sodium [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The observations that the fractions of the ethanol layer decreased and increased the ulcer indices and curative ratios respectively of the treated rats might be attributed to the anti-oxidant vitamin content and proximate composition of the ethanol layer of the chloroform-ethanol extract of the leaves of D. edulis as shown by the results of their analyses. Also, the finding that diclofenac induced ulcer in all the treated rats is in accord with the reports of Verma et al (2011), Santos et al (2012), Wandale et al (2012) and Khan and Khan (2013). The mechanism by which diclofenac and other NSAIDs cause injury to the gastric mucosa is mainly due to the inhibition of cyclooxygenase and suppression of prostaglandinmediated effects on mucosal protection.…”
Section: Discussionsupporting
confidence: 90%
“…The pharmacological activity of NSAIDs is linked to the suppression of prostaglandin biosynthesis from arachidonic acid through inhibiting the enzyme cyclooxygenases [4]. In order to support the results of in vivo study, molecular docking study was executed.…”
Section: Discussionmentioning
confidence: 99%